CHANGES IN CYTOKINES AND ANTIOXIDATIVE MECHANISMS OF THE BRAIN UNDER CONDITIONS OF ELECTRICAL STIMULATIONS OF PALEOCEREBELLAR CORTEX - Godlevsky, L.S.; Stepanenko, K.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Paleocerebellar cortex (nodulus and uvula) was electrically stimulated (ES) in one group of male Wistarrats, while another group was amydalarly kindled and one more group was sham operated. Just only kindledgeneralized clonic-tonic seizures were followed by a net increase of the TNF-. content both in hemispheres (from 34,7+6,0 up to 76,7+6,9 pg/mg of wet brain tissue) and cerebellum (from 106,6+17,7 up to 193,8+29,8 pg/mg of wet tissue) in comparison with data from sham. operated animals. ES of cerebellum (100 Hz) was not followed by changes in TNF-. content both in cortex and cerebellum. Meanwhile, kindling was not followed by changes in thiol/disulfide system changes, but ES of paleocerebellum caused a significant rise offree thiol groups in cortical tissue. Besides, paleocerebellar ES was followed by increase of incorporation ofC14 methionine by ventral hippocampal structures, and H3 triptophane by ventral hippocampus, brain stam and “rest” tissue of brain as well.